Giant Encapsulated Anterior Abdominal Wall Haematoma Complicating Mesh Incisional Hernia Repair: Challenges of Management in a High-Risk Term Pregnancy in a Low Resource Setting - Anwar Sadat Seidu,; David P. Suoseg,; Bernard N. Maanikuu,; Musah Yakubu,; Imoro Osman,; Emmanuel A.N. Azure,; Haruna Danamiji Osman,; John F. Busuuri,; Abdul-Latif Alhassan,; Abdul Aziz Ewura,; Gerald Batariwah,; Munkaila Adam,; et al. (International Journal of Innovative Research in Medical Science, 2021)
Giant encapsulated haematoma of the anterior abdominal wall is an unusual complication of mesh incisional hernia repair. The commonest symptoms are swelling and pain. It can be diagnosed with ultrasonography and Computed Tomography (CT) scan. The objective of this case report is to illustrate the challenges of management of a complex pathology in a high-risk term pregnancy. In this case report, a 28-year-old morbidly obese multiparous woman with two previous ventral wall hernia repairs and two previous caesarian sections, presented at term to the prenatal clinic with protruding anterior abdominal mass. Initial preoperative diagnosis aided by ultrasonography was a herniated term gestation through an incisional hernia. Intraoperatively, the surgical team was faced with the challenge of managing a longstanding giant organized haematoma of the anterior abdominal wall and the anticipation and prevention of obstetric complications associated with two previous caesarian sections and a big baby. This report illustrates that good clinical assessment combined with sonographic assessment of complex cases by an experienced radiologist is crucial to avoid missed diagnosis. A multidisciplinary team management was essential for a successful outcome.